Econophysics and Economics of Games, Social Choices and Quantitative Techniques - Basu, Banasri; Chakravarty, Satya R.; Chakrabarti, Bikas K.; Gangopadhyay, Kausik; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2010)
The combined efforts of the Physicists and the Economists in recent years in analyzing and modelling various dynamic phenomena in monetary and social systems have led to encouraging developments, generally classified under the title of Econophysics. These developments share a common ambition with the already established field of Quantitative Economics. This volume intends to offer the reader a glimpse of these two parallel initiatives by collecting review papers written by well-known experts in the respective research frontiers in one cover. This massive book presents a unique combination of research papers contributed almost equally by Physicists and Economists. Additional contributions from Computer Scientists and Mathematicians are also included in this volume. The book consists of two parts: the first part concentrates on Econophysics problems and the second part stresses on various quantitative issues in Economics. Both parts specialize on frontier problems in Games and Social Choices.
Econophysics of Games and Social Choices -- Kolkata Paise Restaurant Problem in Some Uniform Learning Strategy Limits -- Cycle Monotonicity in Scheduling Models -- Reinforced Learning in Market Games -- Mechanisms Supporting Cooperation for the Evolutionary Prisoner$1 (Bs Dilemma Games -- Economic Applications of Quantum Information Processing -- Using Many-Body Entanglement for Coordinated Action in Game Theory Problems -- Condensation Phenomena and Pareto Distribution in Disordered Urn Models -- Economic Interactions and the Distribution of Wealth -- Wealth Redistribution in Boltzmann-like Models of Conservative Economies -- Multi-species Models in Econo- and Sociophysics -- The Morphology of Urban Agglomerations for Developing Countries: A Case Study with China -- A Mean-Field Model of Financial Markets: Reproducing Long Tailed Distributions and Volatility Correlations -- Statistical Properties of Fluctuations: A Method to Check Market Behavior -- Modeling Saturation in Industrial Growth -- The Kuznets Curve and the Inequality Process -- Monitoring the Teaching $1 (BLearning Process via an Entropy Based Index -- Technology Level in the Industrial Supply Chain: Thermodynamic Concept -- Discussions and Comments in Econophys Kolkata IV -- Contributions to Quantitative Economics -- On Multi-Utility Representation of Equitable Intergenerational Preferences -- Variable Populations and Inequality-Sensitive Ethical Judgments -- A Model of Income Distribution -- Statistical Database of the Indian Economy: Need for New Directions -- Does Parental Education Protect Child Health? Some Evidence from Rural Udaipur -- Food Security and Crop Diversification: Can West Bengal Achieve Both? -- Estimating Equivalence Scales Through Engel Curve Analysis -- Testing for Absolute Convergence: A Panel Data Approach -- Goodwin$1 (Bs Growth Cycles: A Reconsideration -- Human Capital Accumulation, Economic Growth and Educational Subsidy Policy in a Dual Economy -- Arms Trade and Conflict Resolution: A Trade-Theoretic Analysis -- Trade andWage Inequality with Endogenous Skill Formation -- Dominant Strategy Implementation in Multi-unit Allocation Problems -- Allocation through Reduction on Minimum Cost Spanning Tree Games -- Unmediated and Mediated Communication Equilibria of Battle of the Sexes with Incomplete Information -- A Characterization Result on the Coincidence of the Prenucleolus and the Shapley Value -- The Ordinal Equivalence of the Johnston Index and the Established Notions of Power -- Reflecting on Market Size and Entry under Oligopoly.s
Keywords: Economics; Mathematics; Economics/Management Science; Economics general; Game Theory, Economics, Social and Behav. Sciences; Statistical Physics, Dynamical Systems and Complexity